2019
DOI: 10.1111/acv.12511
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem processes, land cover, climate, and human settlement shape dynamic distributions for golden eagle across the western US

Abstract: Species-environment relationships for highly mobile species outside of the breeding season are often highly dynamic in response to the collective effects of everchanging climatic conditions, food resources, and anthropogenic disturbance. Capturing dynamic space-use patterns in a model-based framework is critical as model inference often drives place-based conservation planning. We applied dynamic occupancy models to broad-scale golden eagle Aquila chrysaetos survey data collected annually from 2006 to 2012 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Our analysis and results showed that the presence of golden eagles in coastal southern California was most strongly associated with the spatial arrangement of remote and rugged terrain conditions, developed land cover, and to a lesser extent, scrubland vegetation cover. These findings were in general accordance with predicted habitat associations of golden eagles from previous studies of site occupancy that we used to guide model development (Wiens et al, 2018;Tack et al, 2020). Moreover, our findings echoed those from historical surveys (Dixon, 1937;Scott, 1985) and more recent telemetry studies of individually marked birds (Tracey et al, 2018a(Tracey et al, , 2020 that emphasized the sensitivity of golden eagles to expanding human development.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis and results showed that the presence of golden eagles in coastal southern California was most strongly associated with the spatial arrangement of remote and rugged terrain conditions, developed land cover, and to a lesser extent, scrubland vegetation cover. These findings were in general accordance with predicted habitat associations of golden eagles from previous studies of site occupancy that we used to guide model development (Wiens et al, 2018;Tack et al, 2020). Moreover, our findings echoed those from historical surveys (Dixon, 1937;Scott, 1985) and more recent telemetry studies of individually marked birds (Tracey et al, 2018a(Tracey et al, , 2020 that emphasized the sensitivity of golden eagles to expanding human development.…”
Section: Discussionsupporting
confidence: 89%
“…The field of occupancy estimation and modeling (MacKenzie et al, 2006) provides a rigorous and repeatable framework for monitoring the status of wide-ranging terrestrial wildlife species like golden eagles. Occupancy-based studies focused on monitoring sites (e.g., a territory or other predefined area) have been increasingly used to examine the population dynamics of golden eagles and to evaluate how landscape features or human land use might influence those dynamics (Martin et al, 2009;Stahlecker et al, 2017;Wiens et al, 2018;Tack et al, 2020;Watson et al, 2020). A common strength of these studies is that they accommodate imperfect detection of golden eagles during surveys, which, if not accounted for, can lead to inaccurate inferences about site-use, population status, distribution, or nesting success.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, older transient golden eagles are more susceptible to potentially deadly conflicts with territorial adult birds, influencing their movement decisions as they avoid established territories 38 affecting their landscape of fear and thus their decision landscape overall [39][40][41] . The distri-bution of anthropogenic features could also impact the eagles' decision-making on where to fly 42 . The strong individual variation that we observed in the birds' response to distance to ridge lines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming bald and golden eagles are more numerous in high-quality habitat, it follows then that electrocution risk is greater within high quality habitats (Bedrosian et al 2020, Watts et al 2015. In Lehman et al (2010), the Rangely Oil Field, Uintah Basin, and High Desert study areas each were comprised of medium to high-quality golden eagle habitat (Dunk et al 2019;Tack et al 2020), but habitat variability did not fully account for differences in electrocution rates among poles. This finding suggested that habitat is a component of electrocution risk, but habitat alone cannot determine which poles pose a high risk of electrocution.…”
Section: Habitatmentioning
confidence: 99%